Occurrence of occult hepatitis B virus infection associated with envelope protein mutations according to anti-HBs carriage in blood donors. (March 2020) - Wang, Jiawen; Zhang, Panli; Zeng, Jinfeng; Du, Peng; Zheng, Xin; Ye, Xianlin; Zhu, Weigang; Fu, Yongshui; Candotti, Daniel; Allain, Jean-Pierre; Li, Chengyao; Li, Tingting
Highlights: The characteristics of occult hepatitis B virus infection genotypes B (OBIB ) and C (OBIC ) mutations relating to hepatitis B surface antibody (anti-HBs) elicited by vaccination or the host immune response to hepatitis V virus (HBV) have not been fully explored. Ninety-nine of 310 167 blood donors at Shenzhen Blood Center were identified as having OBI. The occurrence of pre-S/S amino acid substitutions in samples from the 99 blood donors were characterized extensively according to anti-HBs carriage. Some mutations in pre-S/S of OBI were associated with carrier anti-HBs pressure, which was further correlated to the potential emergence of viruses under anti-HBs presence in OBI carriers. Abstract: Objectives: Occult hepatitis B virus infection (OBI) carries a risk of hepatitis B virus (HBV) transmission and hepatocellular carcinoma. As previous studies have had a limited sample size, the characteristics of OBI with genotype B and C (OBIB and OBIC ) mutations relating to hepatitis B surface antibody (anti-HBs) elicited by vaccination or a limited host immune response to HBV have not been fully explored. Methods: In this study, the occurrence of OBIB or OBIC strains associated with envelope protein (pre-S/S) amino acid substitutions obtained from 99 blood donors stratified according to anti-HBs carriage were characterized extensively. Results: According to the presence of anti-HBs within each genotype, the number and frequency of substitution sites specific for anti-HBs(−) OBIB were higher than those specific for anti-HBs(+) OBIB strains (67 vs 31; 117 vs 41), but the reverse pattern was found in OBIC strains (3 vs 24; 3 vs 26). Mutations pre-s1 T68I and sQ129R/L were found uniquely in 15–25% of anti-HBs(+) OBIB carriers and mutation pre-s1 A54E was found preferentially in anti-HBs(+) OBIC, while 17 substitutions were found preferentially in 11–38% of anti-HBs(−) OBIB strains. In the major hydrophilic region (MHR) region, mutations sS167 in OBIB, sT118 in OBIC, and sA166 in both genotypes were possibly immune-induced escape mutation sites. Conclusions: Several mutations in pre-S/S of OBI appeared to be associated with carrier anti-HBs pressure, which might be risk factors for potential reactivation of viruses under anti-HBs selection in OBI carriers.